Comparison of the diagnostic concordance of tele-EMS and EMS physicians in the emergency medical service—a subanalysis of the TEMS-trial - Hess, Patrick P.; Czaplik, Michael; Hess, Johanna; Schröder, Hanna; Beckers, Stefan K.; Follmann, Andreas; Pitsch, Mark; Felzen, Marc (Frontiers in Digital Health, 2025)
IntroductionThe emergency medical services (EMS) in Germany are facing several challenges in the near future. Due to the increasing number of emergency missions, the availability of EMS physicians is becoming more limited, resulting in longer response times. To maintain the high quality of EMS, telemedical support systems have shown potential as a valuable complement to the existing system for specific diagnoses. Since 2014, a tele-EMS system has been implemented in Aachen as an integrated telemedical solution alongside standard EMS. Accurate prehospital diagnosis plays a crucial role in ensuring appropriate hospital admission and reducing the time to clinical treatment for time-sensitive conditions. The main TEMS study demonstrated the overall non-inferiority of tele-EMS physicians compared to on-site EMS physicians. This sub-analysis focuses on comparing the diagnostic accuracy between these two groups.MethodsUp to four prehospital diagnoses were selected, coded according to the ICD-10 system, and compared with all admission and discharge diagnoses.ResultsThe comparison between diagnoses made by tele-EMS physicians and on-site EMS physicians with admission diagnoses showed no significant difference (p = 0.877). Additionally, no significant differences were found for the diagnoses of stroke (p = 0.385) and epileptic seizure (p = 0.738). However, patients from missions where paramedics decided to consult a tele-EMS physician had significantly longer hospital stays compared to those from missions where an on-site EMS physician was initially dispatched (p < 0.001).DiscussionThis randomized controlled analysis demonstrated that there is no difference in diagnostic accuracy between on-site EMS physicians and remote tele-EMS physicians. The significantly longer hospital stays for patients treated by tele-EMS physicians suggest that EMS physicians may be called too frequently for non-severe cases. Clinical Trial Registrationclinicaltrials.gov, identifier (NCT02617875).